Pelaksanaan Klaim Asuransi Pada Asuransi Bumiputra 1912 - endang suparni (Widya Cipta - Jurnal Sekretari dan Manajemen, 2018)
Abstrac- The journey of human life abstract-dalam of course, has always faced with a risk that happens and cannot be predicted before .Every human endeavour to divert the risk to the insurance company . Is to got the rights and able or to function optimally research methodology used writer is the descriptive method with a qualitative approach.berdasarkan the results of research on ajb the earth son of 1912 , then in the process of filing a claim refer to a insurance , especially the administration of an insurance claim as follows: 1 .Filing a claim which is made up of claims approved danklaim may be deferred , 2 .Checking documents , 3 .The process of approval, that a check of administration and financial, 4.penyelesaian payments.Documents that have already received approval and signed by the head of a branch and submitted to part a teller of for the withdrawal of funds claim . In the resolution of claim payments, done 8 ( eight ) working day.When in the process claims there are no obstacles, the finance division submit claim funds to teller for granted to customers, and receipts.As for the types of insurance claim; insurance claim individuals, consisting of a claim to death, a claim to the end of contract and a claim for redemption, while insurance claim a collection of consists of a claim to death, a claim to the end of contract, a claim to redemption, claims for medical expenses by the accident, a claim for in-patient care and surgical operation + outpatient.Also obstacles in payment implementation of insurance claim among other: delay in the process filing a claim insurance, do not bring completeness documents, customers forget check first completeness documents, and loss of policy and receipts proof of payment.